Un centenario olvidado: la ilustración editorial en el siglo xix en colombia (1998)
This article belongs to a larger research project devoted to the originsand devdopment of the art of engraving in Colombia sponsored by theUniversidad Nacional de Colombia. On occasion of the centennial of theRevista Ilustrada, the author surveys the origins of Colombian illuslratedpress, indicating its sources, its interpretations and the originality of itsproductions. In the process of revision of the applications of the graphictechniques used, novelties have ensued in terms of otherwise forgotten books published in Colombia,; diverse topics that inlcude Literature and Music, Geography, Telegraphy, History as well as Infantry Tactics are but a few of the subjects that have been discovered.